Effect of arsenic on tolerance mechanisms of two plant growth-promoting bacteria used as biological inoculants - Armendariz, Ana Laura (2015)
Bacterial ability to colonize the rhizosphere of plants in arsenic (As) contaminated soils is highly important for symbiotic and free-living plant growth-promoting rhizobacteria (PGPR) used as inoculants, since they can contribute to enhance plant As tolerance and limit metalloid uptake by plants. The aim of this work was to study the effect of As on growth, exopolysaccharide (EPS) production, biofilm formation and motility of two strains used as soybean inoculants, Bradyrhizobium japonicum E109 and Azospirillum brasilense Az39. The metabolism of arsenate (As(V)) and arsenite (As(III)) and their removal and/or possible accumulation were also evaluated. The behavior of both bacteria under As treatment was compared and discussed in relation to their potential for colonizing plant rhizosphere with high content of the metalloid. B. japonicum E109 growth was reduced with As(III) concentration from 10. μM while A. brasilense Az39 showed a reduction of growth with As(III) from 500. μM. EPS and biofilm production increased significantly under 25. μM As(III) for both strains. Moreover, this was more notorious for Azospirillum under 500. μM As(III), where motility was seriously affected. Both bacterial strains showed a similar ability to reduce As(V). However, Azospirillum was able to oxidize more As(III) (around 53%) than Bradyrhizobium (17%). In addition, both strains accumulated As in cell biomass. The behavior of Azospirillum under As treatments suggests that this strain would be able to colonize efficiently As contaminated soils. In this way, inoculation with A. brasilense Az39 would positively contribute to promoting growth of different plant species under As treatment.